PELATIHAN TAHSIN AL-QUR`AN SISWA DENGAN MENGGUNAKAN METODE TAKRIR DI MDA PATRIOT PANCASILA MANDAILING NATAL - Elvi Silvia; Martin Kustati; Rezki Amelia (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
This training aims to facilitate and improve the tahsinul Al-Qur'an through the takrir or repetition method at MDA Patriot Pancasila. This tacit or repetition method will make it easier for students at MDA Patriot Pancasila to read and pronounce the letters or verses that they have listened to via audio or from the teacher concerned. This training method was carried out using the Participatory Action Research (PAR) method. In this training, the stages carried out in the takrir method to improve the tahsinul Al-Qur'an are, first by playing audio about the hijaiyah letters and how to pronounce them in accordance with the makharijul letters. After the audio is played, students take turns repeating the correct pronunciation of the hijaiyah letters according to the makhorijul letters. So that students who cannot pronounce the hijaiyah letters correctly according to the makharijul letters will find it easier to understand and remember the pronunciation of reading the hijaiyah letters together, both students are asked to repeat the reading of the hijaiyah letters which have been played alternately. The result of this training is that, with the training carried out, students at MDA Patriot Pancasila are more enthusiastic about repeating, improving and learning about the correct hijaiyah letters and in accordance with the makharijul letters. For the implementation of this training, cooperation between fellow teachers is expected to further improve students' abilities in reciting the Al-Qur'an using the takrir method. In this training, it is hoped that teachers can apply the tahsin of the Al-Qur'an using this takrir method, because it can make it easier for students to understand and remember the tahsin of the Al-Qur'an